The days are just packed a Calvin and Hobbes collection - Watterson, Bill (Kansas City : Andrews and McMeel, 1993)
Aided by his tiger sidekick, Hobbes, Calvin sets out to save the world with his alter egos, Spaceman Spiff and Stupendous Man, while coping with Miss Wormwood, Santa, Susie, and the monsters under his bed.
12 - 17 years
105344
Keywords: Calvin and Hobbes (Comic strip); Calvin (Fictitious character : Watterson) -- Comic books, strips, etc; Hobbes (Fictitious character) -- Comic books, strips, etc; Boys -- Comic books, strips, etc; Imaginary companions -- Comic books, strips, etc; Tiger -- Comic books, strips, etc; Stuffed animals (Toys) -- Comic books, strips, etc; Families -- Comic books, strips, etc; American wit and humor, Pictorial; Wit and humor, Pictorial; Cartoons and caricatures